Neonatal blood pressure before and after delayed umbilical cord clamping. (12th December 2022) - Schenone, Claudio V.; Argoti, Pedro; Goedecke, Patricia; Mari, Giancarlo
Abstract: Objective: To describe values of blood pressure (BP) before and after delayed cord clamping (DCC) in healthy term neonates born to low risk pregnancies, examine differences in the temporal patterns of BP during this transition, and assess potential correlation of these parameters with maternal and perinatal clinical and demographic variables. Methods: Prospective observational study of term infants eligible for DCC born vaginally from uncomplicated pregnancies. Neonatal BP was estimated noninvasively before DCC, at 30 min and 24 h of life. Median, minimum, maximum, mean and standard deviation, as well as percentiles for BP values were calculated. Pearson correlation assessed the correlation between demographic and clinical variables and BP measurements. Spearman correlation studied the association between BP parameters prior to DCC and Apgar scores. Repeated measures ANOVA and Tukey post hoc analyses were used to compare BP measurements over time. A p -value of <.05 was considered significant. Results: A total of 54 patients were included. Mean neonatal birthweight was 3185 g and gestational age 39/3 weeks. The mean values for the systolic, diastolic, and mean BP prior to DCC were 97 ± 24.9 mmHg, 58 ± 21.9 mmHg and 67 ± 27.7 mmHg respectively. A statistically significant difference was detected when comparing BP values obtained before DCC with those measured afterwards (Figure 1 ). A positive correlation was found between SBP and MAP prior to DCC and Apgar scores at 1 min. Conclusion: We describe novel values of BP before DCC in healthy term infants following vaginal delivery. Data suggest that neonates whose cord is clamped in a delayed fashion experience an increase blood pressures immediately after birth, followed by a significant drop within 30 min to levels that remain unchanged at 24 h of life. BP values obtained after DCC in our study are similar to those found by previous authors. Further studies are needed to determine the clinical significance of these findings and assess the potential of BP prior to DCC to evaluate immediate postnatal adaptation. Limitations: Results generalizability may have been limited by varying degrees of neonatal resuscitation, inability to perform more than one measurement before cord clamping ensued, as well as an unequal distribution of self-reported race in our cohort. Also, noninvasive BP estimates have proven less accurate that invasive methods. Finally, our cohort was comprised by a relatively small sample and larger studies will be required to corroborate our findings.